The general equation of a circle with center (a, b) and radius is:

(x - a)^2 + ( y- b)^2 = r^2

The center of the circle in the given problem is (-4 , 2). It passes through (0, 5) So the radius of the circle is sqrt[(0 +4)^2 +(2...

## Read

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The general equation of a circle with center (a, b) and radius is:

(x - a)^2 + ( y- b)^2 = r^2

The center of the circle in the given problem is (-4 , 2). It passes through (0, 5) So the radius of the circle is sqrt[(0 +4)^2 +(2 - 5)^2]

=> sqrt ( 16 + 9)

=> sqrt 25

=> 5

**The equation of the circle is (x +4)^2 + ( y - 2)^2 = 25**